The 2026 Strong El Niño Triggers a Compounding Drought-to-Flood Cascade, Elevating Multisectoral Risks to East African Agriculture and Public Health - Belay Sitotaw Goshu; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2026)
The World Meteorological Organization projects the 2026 El Niño to rank among histories strongest, with an 80% probability of onset between June and August and a 63–65% chance of attaining super-strength from October 2026 through February 2027, posing a dire threat to climate-vulnerable East Africa. This paper provides a holistic, predictive assessment of the event's cascading consequences for agriculture and public health across the region. Our synthesis integrates climatic forecasts from WMO, NOAA, and ICPAC; agricultural and food-security indicators from FAO GIEWS, FEWS NET, and IPC classifications; health surveillance data from WHO; and historical lessons from the 1997–1998 and 2023–2024 episodes. We project a distinct biphasic pattern: drought from June to September curtails planting and growth in western unimodal zones; Ethiopia, Sudan, South Sudan, Uganda, and western Kenya followed by a positive Indian Ocean Dipole-driven deluge from October to December. This second phase unleashes widespread flooding across Kenya, Somalia, southern Ethiopia, and Uganda, destroying standing crops, spoiling stored grain, and rupturing transport and market infrastructure. Staple cereal yields, notably sorghum and millet, could plummet by up to 30%. Concurrently, inundated landscapes amplify Rift Valley fever transmission, triggering substantial livestock losses. The compound effect would push roughly 8.8 million people across 22 high-risk nations into acute food insecurity; Somalia alone may see 6 million individuals facing IPC Phase 3 or worse. Health systems will grapple with surges in cholera, malaria, dengue, and heat-related morbidities, with critical hotspots centering on the Lake Victoria and Tana River basins, the Juba and Shabelle catchments, and densely populated urban hubs like Nairobi. This impending super-El Niño constitutes an unprecedented humanitarian emergency, yet its forecast lead time offers a tangible preparedness window. We urge immediate investments in early-warning system upgrades, climate-resilient crop varieties, irrigation and flood defenses, expanded disease surveillance and vaccine stockpiles, robust water-sanitation-hygiene programs, scaled humanitarian logistics, and targeted interventions addressing the structural poverty and land-use pressures that magnify climatic shocks.